2023
DOI: 10.1038/s42255-023-00834-7
|View full text |Cite
|
Sign up to set email alerts
|

Human resident liver myeloid cells protect against metabolic stress in obesity

Abstract: Although multiple populations of macrophages have been described in the human liver, their function and turnover in patients with obesity at high risk of developing non-alcoholic fatty liver disease (NAFLD) and cirrhosis are currently unknown. Herein, we identify a specific human population of resident liver myeloid cells that protects against the metabolic impairment associated with obesity. By studying the turnover of liver myeloid cells in individuals undergoing liver transplantation, we find that liver mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…[18,19] Furthermore, using liver spheroids we functionally dissected the crosstalk between hepatocytes and liver macrophages in MASLD [47,48] and could identify roles of subpopulations of myeloid in curbing hepatic metabolic stress in obesity. [49] However, comprehensive phenotypic profiling of this model at the proteome level had so far been limited due to the high cell numbers required for conventional proteomics. Importantly, we here found that protein extraction using repeated freeze-thaw cycles was identified to outperform chemical lysis methods by over 40%.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] Furthermore, using liver spheroids we functionally dissected the crosstalk between hepatocytes and liver macrophages in MASLD [47,48] and could identify roles of subpopulations of myeloid in curbing hepatic metabolic stress in obesity. [49] However, comprehensive phenotypic profiling of this model at the proteome level had so far been limited due to the high cell numbers required for conventional proteomics. Importantly, we here found that protein extraction using repeated freeze-thaw cycles was identified to outperform chemical lysis methods by over 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests a role for cellular networks that crosstalk with our immune cells and gut microbiota in facilitating chronic liver disease progression. For example, a recent study on NAFLD and cirrhosis described a subpopulation of human resident liver myeloid cells (LM) that were protective against obesity-associated OxS development [ 42 ]. LMs were shown to upregulate Peroxiredoxin 2 (PRDX2), a biological catalyst that reduces hydrogen peroxide, organic hydroperoxides, and peroxynitrite, essential for detoxifying harmful compounds.…”
Section: Oxs In Other Liver Diseasesmentioning
confidence: 99%
“…Compared to the dogma from murine parabiosis models where tissue residency is long-lasting ( 4 ), solid organ transplantation studies in humans have revealed an alternative picture with a greater degree of immune cell reconstitution over time ( 58 ). However, the reconstitution rate appears to be organ and cell-type specific with more rapid reconstitution of liver myeloid and lymphoid cells ( 7 , 8 ) whilst intraepithelial T cells remain donor-derived for longer periods of time after lung and intestinal transplantation ( 5 , 6 , 9 ) as well as of host origin in skin after hematopoietic stem cell transplantation (HSCT) ( 10 ). Yet, for other organs, if and under what circumstances immune reconstitution occurs remains elusive.…”
Section: Introductionmentioning
confidence: 99%